Szczególne opłaty administracyjne - Antonów, Dobrosława (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
Charges for official actions of the public administration (particular management fees) have been described in the book. There are lots of such types of charges in Polish legal order; the charges have different names and diverse subject and legal construction. Regulations by law, concerning the charges, are scattered in many legal acts rated among the public law. The essence and characteristics of the particular management fees, as well as the concept of distinguishing the fees among public duties (chapter I) have been discussed in the book. The author’s concept of research (methods and purposes) on the group of the fees (chapter II) has also been discussed in the book. The analysis of Polish legal order aimed at indicating most management fees and describing the legal construction of the fees are the fundamental part of the book. The fees are divided into fees distinguished on account of the kind of the official action being subject to a fee (chapter III) and on account of the agency taking up the action which is subject to fee (chapter IV). The construction of more than 100 management fees with taking into consideration over 170 legal acts have been indicated and discussed in the book. The analysis has been summed up by the system assessment of particular management fees in Polish legal order and conclusions on the subject of current condition of Polish legislation in the scope, as well as the postulates of changes for the future (chapter V and conclusion).
Keywords: charge; public charge; management fee; charge for official actions; official actions; administrative actions; public administration; payment for official actions; particular management fees; passport fees; consular fees; air charges; registration charges; register charges; fee for passing a concession; fee for passing a permit; fee for passing a licence; licence fee; fee for entry in a registe; fee for entry in a record; fee for extract from a register; fee for extract from a record; fee for passing a certificate